2016
DOI: 10.1007/s13142-016-0385-9
|View full text |Cite|
|
Sign up to set email alerts
|

Reach and representativeness of ethnic minority women in the Health Is Power Study: a longitudinal analysis

Abstract: Reach is a key factor in translating research to practical application. This study examined reach and representativeness of a multi-city, randomized controlled community health trial in African American (AA) and Hispanic or Latina (HL) women. Participants completed measures of demographics, body mass index (BMI), percent body fat, resting heart rate, and blood pressure followed by a run-in procedure and a randomization meeting. AA were more likely to be screened out initially; HL were more likely to drop out. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…After women were recruited, they completed a run in procedure as described below to avoid assigning women to groups who might be more likely to drop out, resulting in a sample of 310 women assigned to groups. A total of 198 women completed post-intervention measures, representing 64% of those assigned, which compares favorably to other studies of ethnic minority women (Lee et al, 2016). Of these, 132 had complete data on all measures, and these cases were used for analyses.…”
Section: Methodsmentioning
confidence: 49%
See 1 more Smart Citation
“…After women were recruited, they completed a run in procedure as described below to avoid assigning women to groups who might be more likely to drop out, resulting in a sample of 310 women assigned to groups. A total of 198 women completed post-intervention measures, representing 64% of those assigned, which compares favorably to other studies of ethnic minority women (Lee et al, 2016). Of these, 132 had complete data on all measures, and these cases were used for analyses.…”
Section: Methodsmentioning
confidence: 49%
“…HIP was implemented in Houston and Austin, Texas from 2006 to 2008. Women were recruited using a variety of strategies including face-to face announcements at community meetings and events, advertisements in local media (Lee et al, 2016). Participants were randomly assigned to a PA group or vegetable and fruit comparison group.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, there were no significant differences by recruitment method or city, but overall participants were overrepresented by higher educated, wealthier, and older women (50,57). Future research on recruitment strategies to address disparities and equity would be appropriate (50,57).…”
Section: Reachmentioning
confidence: 89%
“…Additionally, the intervention effectively enrolled the population prioritized for these programming services–in this case low-income Latinos. This is a key component of “Reach” from the RE-AIM Framework which is not regularly or accurately reported in Community based interventions, and when it is, there is evidence that the prioritized groups are over or under-represented ( 50 , 57 ). For example, in one worksite wellness intervention, employees from higher income households, with higher education levels and health literacy proficiency were significantly more likely to participate in the program ( p < 0.01) ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other studies have indicated that women are significantly more likely than men to drop out early from healthcare services [39]. Additionally, a study found that women who completed all stages of the research had a different profile than women who completed only the initial assessments [40]. Traditionally, women are more likely to internalize their emotions than men, while men are more likely to externalize them [41].…”
Section: Discussionmentioning
confidence: 99%